CONTRIBUTION OF STUDENTS FROM OTHER LOCATIONS TO THE ECONOMY OF RI-OBAMBA. CASE - FINANCE CAREER - SLUSARCZYK ANTOSZ, MARIA; GAVILÁNEZ ALVAREZ, OSCAR DANILO; VALLEJO SÁNCHEZ, DIEGO PATRICIO (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019, 2020)
Nowadays about 60% of the Finance School students   come from outside Riobamba city. The objective of this work was to know the contribution of these students to the economy of Riobamba. The consumption habits and the sources of income of the university students who constituted the object of study were analyzed. Theoretically, topics related to the economics of education and the role of consumption in the economy were studied. The method applied was a cross-sectional study with a sample population of 150 students from the Finance School in September 2019. A questionnaire with 20 closed questions was applied to obtain information about details of income and expenses of the students. The main results obtained show that on average, a student who come from another city wastes around 230 dollars per month in rent, food, transportation, study materials, telephone, etc. It was concluded that students who come from outside Riobamba contribute significantly to the economy of the city, not to mention that only the Finance School students consume $ 82,570.00 per month.